Pulses value chain in Ethiopia: Constraints and opportunities for enhancing exports - Rashid, Shahidur; Yirga, Chilot; Behute, Befekadu; Lemma, Solomon (International Food Policy Research Institute, 2010)
This report provides an analysis of the critical role of pulses in agricultural production as a driver for economic growth and food security. Pulses, which occupy approximately 13 percent of cultivated land and account for approximately 10 percent of the agricultural value addition, are critical to smallholder livelihoods in Ethiopia. Pulses contribute to smallholder income, as a higher-value crop than cereals, and to diet, as a cost-effective source of protein that accounts for approximately 15 percent of protein intake. Moreover, pulses offer natural soil maintenance benefits through nitrogen-fixing, which improves yields of cereals through crop rotation, and can also result in savings for smallholder farmers from less fertilizer use.